Integration of quality management systems in chemical laboratory - Branská, Lenka; Markovič, Lukáš (University of Pardubice, 2013)
Given the increasing demands of customers in logistic chains for quality (of products and services), it is necessary to constantly improve business quality management systems. These can assume different forms in different businesses. In most cases, they are only based on the ISO 9000 standards, but we can often see a company that has several parallel systems of quality management built on the basis of several methodological guidelines. This allows it to obtain a few certificates and, also with the help thereof, extend the range of their customers, but it complicates their practical application in the business practice. Therefore, it is a natural tendency of managers to integrate them into a coherent quality management system that supports the daily execution of business activities. The professional literature addresses the integration of individual management systems (i.e., quality management system, environmental management system and management of health and safety at work), where however the solution is facilitated by compatibility of methodological guidelines. In principle, the problem of integrating parallel-standing quality management systems has not been addressed in the literature yet. Therefore, the present paper deals with this form of integration. It addresses how to integrate in a chemical laboratory several parallel quality management systems built on the basis of various methodological guidelines.